1995
DOI: 10.1192/bjp.167.4.507
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Brief Episodes with Psychotic Features in Adolescence: Periodic Psychosis of Puberty Revisited

Abstract: Recurrent brief episodes in adolescence tend to show a near-monthly rhythm and psychotic features. Most of them appear to the manifestations of affective illness and may be treated and prevented as such.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…Fourteen cases of psychoses were associated with menarche (48,52,(57)(58)(59)(60)(61)(62)(63)(64). Formerly defined as psychosis of puberty or adolescence (65), menarcheassociated-psychoses first emerged just before the first menstruation of the adolescent, with the onset of the first psychotic episode immediately followed by the first menses.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen cases of psychoses were associated with menarche (48,52,(57)(58)(59)(60)(61)(62)(63)(64). Formerly defined as psychosis of puberty or adolescence (65), menarcheassociated-psychoses first emerged just before the first menstruation of the adolescent, with the onset of the first psychotic episode immediately followed by the first menses.…”
Section: Resultsmentioning
confidence: 99%
“…'s study (25), three women who responded best to lithium had the diagnosis of cyclothymic disorder. In another study (26), a sub‐group of adolescent girls with periodic episodes related to one phase of menstrual cycle, experienced no recurrences while on lithium. Some researchers suggested that breakthrough symptoms during the premenstrual phase might be linked to subtherapeutic serum lithium levels in women with BD and improved drug response and more stable clinical course might be obtained if serum lithium levels were monitored for premenstrual decline (27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…This serves to highlight the centrality of mania in BD and the potentially explanatory role of oxytocin in the disorder, as discussed by Crespi’s (2016) examination of the ‘symmetrical’ comorbidities of ASD and polycystic ovarian syndrome (PCOS) on the one hand and BD and endometriosis on the other, proposed to be the results of decreased and increased oxytocin levels, respectively (though PCOS comorbidity with BD has also been reported by Qadri et al, 2018). Menstrual psychosis is also thought to be a manifestation of BD pathology (Abe and Ohta, 1995; Brockington, 2005, 2011), and menses can trigger exacerbation of psychosis in BD and other psychotic disorders (Reilly et al, 2019).…”
Section: Domestication Features In Bdmentioning
confidence: 99%